2023
DOI: 10.3390/foods12071379
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Acid Whey Addition and Ultrasonic Treatment on the Chemical and Microbiological Stability of Lamb Stuffing

Abstract: The microbiological and chemical stability of stuffing is crucial in meat processing. Small ruminant (lamb) meat has many nutritional advantages (fatty acid composition and ratio, high biological value of protein, source of zinc, and selenium) but is poorly utilized in processing. In this experiment, we determined the effects of physical (sonication), chemical (salt, curing salt, and air access), and microbiological (acid whey) factors on the microbiological and chemical stability of lamb meat stuffing. Proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…The protein values found for cattle in the study were similar to some of the values found in the researches (Hamed Hammad Mohammed et al, 2020;Pouzo et al, 2023;Santana et al, 2023), higher than some (Salim et al, 2023) and lower than some (Oliveira et al, 2021;Ngom et al, 2022). While the values reported for sheep were in agreement with (Costa et al, 2009;Romero-Bernal et al, 2017;Radzik-rant et al, 2023) or higher than literature reports and findings (Mioč et al, 2007;Lima et al, 2022;Latoch et al, 2023;Lunesu et al, 2023;Uushona et al, 2023). The rates found for chicken meat were higher than the reported values Xu et al, 2021;Sugiharto et al, 2022;Weng et al, 2022;Fathi et al, 2023).…”
Section: Figure 2 Ash Content Of Meat Samples Obtained From Different...supporting
confidence: 86%
See 1 more Smart Citation
“…The protein values found for cattle in the study were similar to some of the values found in the researches (Hamed Hammad Mohammed et al, 2020;Pouzo et al, 2023;Santana et al, 2023), higher than some (Salim et al, 2023) and lower than some (Oliveira et al, 2021;Ngom et al, 2022). While the values reported for sheep were in agreement with (Costa et al, 2009;Romero-Bernal et al, 2017;Radzik-rant et al, 2023) or higher than literature reports and findings (Mioč et al, 2007;Lima et al, 2022;Latoch et al, 2023;Lunesu et al, 2023;Uushona et al, 2023). The rates found for chicken meat were higher than the reported values Xu et al, 2021;Sugiharto et al, 2022;Weng et al, 2022;Fathi et al, 2023).…”
Section: Figure 2 Ash Content Of Meat Samples Obtained From Different...supporting
confidence: 86%
“…Carcass score is also one of the parameters to be taken into account as it affects fatness (Rubayet Bostami et al, 2018). The fat values presented in the literature reports were similar (Romero-Bernal et al, 2017), lower (Mioč et al, 2007), or higher (Junkuszew et al, 2020;Lima et al, 2022;Latoch et al, 2023) for lambs; higher for beef (Rubayet Bostami et al, 2018;Hamed Hammad Mohammed et al, 2020;Ngom et al, 2022;Santana et al, 2023); higher Xu et al, 2021) and similar (Weng et al, 2022;Fathi et al, 2023) for chicken; similar (Cardinali et al, 2015;Dalle Zotte et al, 2018;Kumar et al, 2023) and higher (Haque et al, 2016;Frunză et al, 2023;Neagu et al, 2023;Nutautaitė et al, 2023) for rabbit meat.…”
Section: Figure 2 Ash Content Of Meat Samples Obtained From Different...mentioning
confidence: 99%
“…Meat and meat products are not only a source of nutrients for humans [1,2], but also an excellent substrate for the development of many microorganisms [3]. Fresh meat is always exposed to the action of many species of microorganisms, causing deterioration of its sensory quality and limiting its usefulness, both culinary and technological.…”
mentioning
confidence: 99%
“…The microbiological quality of meat is important both for consumers and from a safety point of view. Meat can be a habitat for saprophytic and pathogenic microorganisms that can deteriorate its quality or threaten the safety of consumers [1,4].…”
mentioning
confidence: 99%